Interprovincial food trade aggravates China’s land scarcity - He, Jianjian; Wang, Siqi; Heijungs, Reinout; Yang, Yi; Shu, Shumiao; Zhang, Weiwen; Xu, Anqi; Fang, Kai (Springer, 2024)
Land is an increasingly scarce resource that plays a critical role in achieving many Sustainable Development Goals (SDGs). Land scarcity, namely the imbalance state between cropland availability and demand, can be mitigated by the trade of agricultural products, but how effective it is remains unclear. Here, by integrating grid-level data on cropland into multi-regional input–output analysis, this paper accounts for the scarce land footprint and virtual scarce land flows within China at a 1 km × 1 km resolution. Results show that over 70% of China’s land footprint and scarce land footprint can be attributed to less than 20% of the land, and nearly 38% of the land footprint and scarce land footprint hotspot clusters are found to cross provinces. Generally, while virtual land trade mitigates the land scarcity of land-importing provinces by 50.8%, it disproportionately aggravates the land scarcity of land-exporting provinces by 119.8%. These findings challenge the dominant thinking about food trading and call for new policies to improve land resources management and promote collaborative governance across administrative boundaries. Our study also highlights the critical importance of considering land scarcity, shedding lights on how it may be integrated into environmental footprints to better assist the SDG framework.